Design of a total quality management system applicable to pharmacies of the public health network of Ecuador - Mazacón Solano, Willy Ramón; Mariscal Santi, Walter; Jiménez Jiménez, William (Revista Universidad de Guayaquil, 2021)
Good Practices in a universal framework establish quality control as a key in the proper management of a clinical or hospital pharmacy beyond being a means of verification. The administration of the total quality of medicines in the hospital field involves the collaboration of the integral health team, where the pharmaceutical professional not only has a role framed in being a specialist in medicines, but also the services provided by his department at the hospital are rooted in the framework of total quality (TC). This approach based on TC administration far exceeds the occupations commonly performed by the personnel currently working in most hospitals nationwide, so both new and existing processes have to adjust to this new paradigm. The present work through the development of a total quality management manual applicable to hospital pharmacies of the Comprehensive Public Health Network (RPIS) in Ecuador seeks to provide the basic guidelines for the design of a TC management system applicable to pharmacies of Basic Hospitals (Category II-4) and General Hospitals (Category II-5) of the second level of hospital care of the RPIS.